The dynamics of proximal femoral nails: A clinical comparison between PFNA and Targon PF - Wild, Michael; Jungbluth, Pascal; Thelen, Simon; Laffrée, Quirine; Gehrmann, Sebastian; Windolf, Joachim; Hakimi, Mohssen; Betsch, Marcel (Orthopedics, 2010)
The objective of this study comparing the proximal femoral nails Targon PF (Aesculap, Tuttlingen, Germany) and Proximal Femoral Nail Antirotation (PFNA; Synthes. Oberdorf, Switzerland) was to observe the complications and postoperative results following pertrochanteric femoral fracture fixation, with special attention devoted to the dynamic properties of both implants under physiological load in vivo. The survey was designed as a randomized, prospective study of 80 patients who had sustained a pertrochanteric femoral fracture (AO type 31.A2). Postoperative radiological and clinical examinations were conducted over a period of 12 months on 40 respective patients treated with a PFNA or a Targon PF nail. Average operative time was 66.2 minutes and average fluoroscopy time was 103.6 seconds in the PFNA group, which was significantly lower than in the Targon PF group (84.7 minutes and 164.5 seconds, respectively). No significant difference was found between the 2 groups in terms of range of motion (P=.26) or Harris Hip Score (P=.83). The femoral neck components of the Targon PF showed a significantly higher sliding ability (14.5 mm; P=.04) than the PFNA (11.1 mm). Both implants are suited to treat pertrochanteric femoral fractures and display comparable clinical results. The Targon PF demonstrates better dynamic properties than the PFNA under physiological load in vivo. A disadvantage of the Targon PF, however, is the more complicated surgical technique and the longer operative time.
CRIS-Team Scopus Importer:2022-07-20